2012
DOI: 10.1155/2012/282959
|View full text |Cite
|
Sign up to set email alerts
|

The Variation in the Absence of the Palmaris Longus in a Multiethnic Population of the United States: An Epidemiological Study

Abstract: The absence of the palmaris longus (PL) has been shown to vary based on body side, gender, and ethnicity. In prior studies, homogenous ethnic populations have been shown to have differences in rates of absence. However, no study thus far has analyzed the differences in palmaris longus prevalence in a multiethnic population. We prospectively collected data on 516 patients visiting the outpatient hand clinics at LAC+USC Medical Center and Keck Medical Center. Analysis of the data was then performed for variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 17 publications
2
30
0
3
Order By: Relevance
“…The prevalence of agenesis was found to be significantly more common on the left side [3,34]. This corresponds to our study, in which four subjects had a unilateral PLM on the right side while only two subjects showed a unilateral PLM on the left side.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of agenesis was found to be significantly more common on the left side [3,34]. This corresponds to our study, in which four subjects had a unilateral PLM on the right side while only two subjects showed a unilateral PLM on the left side.…”
Section: Discussionsupporting
confidence: 90%
“…Thompson et al reported that men were more prone to have a bilateral and unilateral absence of the PLM, but this was not statistically significant [27]; other authors reported the incidence of agenesis to be higher in women [1,26,34].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Seven studies reported the overall PLA rate in Africans (Kayode et al, ; Gangata, ; Mbaka et al, ; Ndou et al, ; Kigera and Mukwaya, ; Soltani et al, ; Venter et al, 2013) with a total of 3,907 subjects. The pooled proportion of the random effects distribution for studies of PLA was 11.3% (95% CI = 0.037–0.222) with Q = 499.52, df = 6, P < 0.0001, I 2 = 98.8%.…”
Section: Resultsmentioning
confidence: 99%
“…Muscle agenesis is a rare anomaly, being the agenesis of palmar longus the most frequently reported in the literature, with an overall incidence of 15 % (Htwe et al, 2012) (Sankar et al, 2011) and 13.1 % in the Hispanic population (Soltani et al, 2012). As for the absence of the Medial Gastrocnemius Muscle (MGM), there is not sufficient evidence of its incidence and only have been described case reports, while Plantar Muscle (PM), is estimated to be 7-20 % (Aragão et al, 2010& Kwinter et al, 2010.…”
Section: Introductionmentioning
confidence: 99%